The development of Bojongsari Water Attractions (Owabong) - Solahuddin Kusumanegara; M. Soebiantoro; Triana Ahdiati (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The local government of Purbalingga and society develops Owabong to increase their economic condition. The development has set as a model for other regions. This study aims to describe the policy evaluation of Owabong development as a leading tourist attraction in Purbalingga, Central Java. The study uses a qualitative method with a case-study approach equipped with quantitative data in the form of survey results— the data collected through the observation, in-depth interviews, and document studies. There are 15 informants taken purposively for the interviews, and 76 respondents were randomly selected for the survey sample. The research uses the interactive analysis technique from Miles & Huberman and descriptive statistics analysis to analyze it. The result shows that a low Human Development Index (HDI) associated with a low economic level encourages the government to develop tourism in Purbalingga. The compilation of the particular regulation on Owabong becomes the basis for planning leading tourism development and its implementation compiled by the authorities (87.72%). Based on the regional regulation, the local government, through the regional company of Owabong, succeeds in developing Owabong as a leading tourist attraction and has a positive impact on the local government itself as well as the surrounding communities. Throughout 2016, the regional company of Owabong has contributed to the original regional income of Purbalingga up to 6.684.178.335 IDR. The existence of Owabong has guaranteed business opportunities to the surrounding communities (85%) and increased their income (90%), the level of community support for the existence of Owabong is 100%, the leaders have succeeded in establishing the cooperation of top and bottom line (82.46%). The main factors of being successful are the existence of special regional regulation on leading tourist attractions managed by regional companies, apparatus compliance in carrying out the development as planned, the support from the communities around the tourism object, and leadership. So, the policy of developing tourism through regional regulation before a leading tourist attraction has successfully achieved the goals. In conclusion, the government has succeeded in using social capital as well as the power to reach the goals.